THE LEARNING STRATEGIES OF TAIWANESE UNIVERSITY STUDENTS: ENGLISH MAJORS VERSUS NON-ENGLISH MAJORS AND MALES VERSUS FEMALES - Yueh-miao Chen (Indonesian JELT, 2005)
This study intends to investigate the learning strategies of Taiwanese university students. Two groups of students – 66 English majors and 86 non-English majors – were the subjects of the study. They responded to the Strategy Inventory for Language Learning (SILL) (Oxford, 1989) of ESL or EFL version of 50 questions. The responses were calculated through statistical analysis in terms of frequency, mean, and standard deviation. It was found that all subjects use compensation strategies most frequently, and affective ones most infrequently. When English majors were compared with non-English majors, the former used learning strategies more frequently than the latter. Similarly, when  gender was compared, female students tended to apply learning strategies more frequently than male students did. The top one and two strategies employed by all subjects were “If I can’t think of an English word, I use a word or phrase that means the same thing,” and “To understand unfamiliar English words, I make guesses.” The strategy least used was “I write down my feelings in a language learning diary.” The paper concludes by discussing the pedagogical implications of the findings. Keywords: EFL learners,  EFL  university  students,  learning strategies